Survival of the thickest - Buteau, Michelle (Gallery Books, 2020)
Buteau's humorous essays reflect on growing up Caribbean, Catholic, and thick in New Jersey, going to college in Miami (where everyone smells like pineapple), her many friendship and dating disasters, working as a newsroom editor during 9/11, getting started in standup opening for male strippers, marrying into her husband's Dutch family, IVF and surrogacy, motherhood, chosen family, and what it feels like to have a full heart, tight jeans, and stardom finally in her grasp.